Association between early airway intervention in the pre-hospital setting and outcomes in out of hospital cardiac arrest patients: A post-hoc analysis of the Target Temperature Management-2 (TTM2) trial - Battaglini, Denise; Schiavetti, Irene; Ball, Lorenzo; Jakobsen, Janus Christian; Lilja, Gisela; Friberg, Hans; Wendel-Garcia, Pedro David; Young, Paul J; Eastwood, Glenn; Chew, Michelle S; Unden, Johan; Thomas, Matthew; et al. (Resuscitation, 2024)
INTRODUCTION: Airway management is a critical component of out-of-hospital cardiac arrest (OHCA) resuscitation. The primary aim of this study was to describe pre-hospital airway management in adult patients post-OHCA. Secondary aims were to investigate whether tracheal intubation (TI) versus use of supraglottic airway device (SGA) was associated with patients' outcomes, including ventilator-free days within 26 days of randomization, 6 months neurological outcome and mortality. METHODS: Secondary analysis of the Target Temperature Management-2 (TTM2) trial conducted in 13 countries, including adult patients with OHCA and return of spontaneous circulation, with data available on pre-hospital airway management. A multivariate logistic regression model with backward stepwise selection was employed to assess whether TI versus SGA was associated with outcomes. RESULTS: Of the 1900 TTM2 trial patients, 1702 patients (89.5%) were included, with a mean age of 64 years (Standard Deviation, SD = 13.53); 79.1% were males. Pre-hospital airway management was SGA in 484 (28.4%), and TI in 1218 (71.6%) patients. At hospital admission, 87.8% of patients with SGA and 98.5% with TI were mechanically ventilated (p < 0.001). In the multivariate analysis, TI in comparison with SGA was not independently associated with an increase in ventilator-free days within 26 days of randomization, improved neurological outcomes, or decreased mortality. The hazard ratio for mortality with TI vs. SGA was 1.06, 95%Confidence Interval (CI) 0.88-1.28, p = 0.54. CONCLUSIONS: In the multicentre randomized TTM2-trial including patients with OHCA, most patients received prehospital endotracheal intubation to manage their airway. The choice of pre-hospital airway device was not independently associated with patient clinical outcomes. TRIAL REGISTRATION NUMBER: NCT02908308.
Keywords: Female; lidé středního věku; urgentní zdravotnické služby; zástava srdce mimo nemocnici; mužské pohlaví; Out-of-Hospital Cardiac Arrest; zajištění dýchacích cest; Humans; Airway Management; intratracheální intubace; Hypothermia, Induced; Emergency Medical Services; kardiopulmonální resuscitace; Cardiopulmonary Resuscitation; lidé; terapeutická hypotermie; Middle Aged; senioři; ženské pohlaví; Aged; Intubation, Intratracheal; Male